Exploring the Strong Interaction of Three-Body Systems at the LHC - S. Acharya; D. Adamová; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; M. Al-Turany; D. Aleksandrov; et al. (Physical Review X, 2024)
Deuterons are atomic nuclei composed of a neutron and a proton held together by the strong interaction. Unbound ensembles composed of a deuteron and a third nucleon have been investigated in the past using scattering experiments, and they constitute a fundamental reference in nuclear physics to constrain nuclear interactions and the properties of nuclei. In this work, K^{+}-d and p-d femtoscopic correlations measured by the ALICE Collaboration in proton-proton (pp) collisions at sqrt[s]=13  TeV at the Large Hadron Collider (LHC) are presented. It is demonstrated that correlations in momentum space between deuterons and kaons or protons allow us to study three-hadron systems at distances comparable with the proton radius. The analysis of the K^{+}-d correlation shows that the relative distances at which deuterons and protons or kaons are produced are around 2 fm. The analysis of the p-d correlation shows that only a full three-body calculation that accounts for the internal structure of the deuteron can explain the data. In particular, the sensitivity of the observable to the short-range part of the interaction is demonstrated. These results indicate that correlations involving light nuclei in pp collisions at the LHC will also provide access to any three-body system in the strange and charm sectors.